The Effects of ICT-Based Social Media on Ethica Communication Motivation - Al Ihwanah (Jurnal Mantik, 2022)
The use of the internet, especially social media applications, is now seen as public consumption. Most of modern society has been addicted and dependent on the internet. The thing that needs attention is what benefits are obtained from social media that need to be classified. A social problem was born when today's children have addiction and dependence on the use of social media. From the survey that has been conducted, various negative impacts emerge and trigger social problems for children in Indonesia. Most of the children in Indonesia actively use the internet and most of these children use social media as the dominant interaction in using the internet. The effects of ICT-based social media need attention. Unsupervised use of social media has the effect of decreasing ethical communication motivation. It is this impact that is felt that needs attention and immediately gets a response from the closest environment as the role and control of the closest person is able to become a filter for children to use social media.